An enveloped virus-like particle vaccine expressing a stabilized prefusion form of the SARS-CoV-2 spike protein elicits highly potent immunity. Issue 35 (16th August 2021) - Fluckiger, Anne-Catherine; Ontsouka, Barthelemy; Bozic, Jasminka; Diress, Abebaw; Ahmed, Tanvir; Berthoud, Tamara; Tran, Anh; Duque, Diane; Liao, Mingmin; McCluskie, Michael; Diaz-Mitoma, Francisco; Anderson, David E.; et al.
Highlights: VBI-2902a is a VLP-based vaccine candidate against SARS-COV-2. VBI-2902a contains VLPs pseudotyped with a modified prefusion SARS-COV-2 S in Alum. VBI-2902a induces robust neutralization antibody responses against SARS-COV-2 S. VBI-2902a protects hamsters from SARS-CoV-2 induced lung inflammation. A single dose of VBI-2902a provides protective benefit in hamsters. Abstract: We evaluated enveloped virus-like particles (eVLPs) expressing various forms of the Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) spike protein and several adjuvants in an effort to identify a highly potent Coronavirus disease 2019 (COVID-19) vaccine candidate. eVLPs expressing a modified prefusion form of SARS-CoV-2 spike protein were selected as they induced high antibody binding titers and neutralizing activity after a single injection in mice. Formulation of SARS-CoV-2 S eVLPs with aluminum phosphate resulted in balanced induction of IgG2 and IgG1 isotypes and antibody binding and neutralization titers were undiminished for more than 3 months after a single immunization. A single dose of this candidate, named VBI-2902a, protected Syrian golden hamsters from challenge with SARS-CoV-2 and supports the on-going clinical evaluation of VBI-2902a as a highly potent vaccine against COVID-19.